Educação permanente em gerontologia para agentes comunitários de saúde - Placideli, Nádia [UNESP] (2013)
The increasing proportion of elderly causes implications such as the growing number of diagnoses of chronic diseases, which in most cases are handled by the Unified Health System (UHS). In some Brazilian cities, the primary health care is carried out through the Family Health Strategy (FHS). Among the professionals who work in the FHS, the Community Health Agents (CHA) stand out, since they are key players in the team, setting up the communication link with the community. Regarding the elderly, an agent can greatly contribute to improve their life quality. In this context, this study aimed to study an Education Program in Gerontology to the Community Health Agents, in a small town in the state of São Paulo. It also had as a purpose to analyse the profile sociodemographic of the CHA, to know the formal and informal contact of the elderly group with the CHA and to evaluate successes and failures of the test on gerontological knowledge applied before and after the development of the Education Program in Gerontology. This research follow the ethical aspects, since all subjects involved signed a consent form and it was approved by the ethical committee for research (FMB-UNESP), under the protocol CEP 4149-2012. The survey involved 86 participants and it had a total of 25 lost subjects. The results regarding the socioeconomic profile, showed a predominance of females ( 90.7%), an average age of was 34 years old, mostly married (53.4%), education level of high school (79%), average family income of three minimum salary and average working time of 31 months as CHA. Regarding the description of the CHA contact with the elderly groups, most of the agents have an elderly member in the family (87.2%) and has lived or lives with an elderly (62.7%), they stated that they have always had some kind of contact with the elderly (95,3%), both in the family and at work (77.9%). Most of them believe to have enough experience to work with the elderly (93%), ...